Three dimensional unsteady heat and mass transport from six porous moist objects in a channel under laminar forced convection - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2021)
Three dimensional unsteady heat and mass transport features for six identical porous moist objects are studied in a channel with hot dry air under laminar flow conditions. Direct coupling between the channel flow and porous moist objects is considered while the governing equations for flow in channel domain and heat and mass transport in porous moist objects are solved simultaneously. In this case, specification of local heat and mass transfer coefficients on the porous object boundaries is not needed and it is accurate since these coefficients are time dependent and spatially varying along the objects when multiple porous objects in three dimensional unsteady configuration are considered. Numerical simulations are performed with Galerkin weighted residual finite element method. The simulation is performed for varying values of hot air velocities (between 0.15 m/s and 0.5 m/s), inlet temperatures (between 303 K and 343 K) and spacing between the moist objects in the flow direction (between 0.4H and 0.9H). The impact of the spacing on the heat and mass transfer features is profound for the last block in the array (B5) while it has slight impact on the first two blocks (B1 and B2) in the array. The variation in the reduced moisture content is 13% for block B5 while it is only 2% for block B1 when cases with the lowest and highest distances are compared. Hot dry air temperature has the most impact on the moisture reduction for the first two blocks B1 and B2 while the velocity impact is very influential for the last block B5. As the lowest and highest hot air temperatures are compared, 33% rise in the reduced moisture content is obtained for block B2, but it is only 12% for block B5. An efficient modeling strategy based on proper orthogonal decomposition is used for the approximation of temperature and vapor concentration in the computational domain with 10 modes for temperature and 45 modes for vapor concentration.
Keywords: Porous moist; 3D unsteady; Convective drying; CFD; POD